Machine condition recognition via hidden semi-Markov model - Yang, Wenhui; Chen, Lu (Computers & industrial engineering, 2021)
In intelligent manufacturing systems, machines are subject to condition deterioration.Identifying machine condition is crucial for making practical decisions in production management. This paper studies the machine condition recognition problem in wafer fabrication. A sequence of processing times collected from past production is used to train a hidden semi-Markov model (HSMM). To improve the precision of the HSMM in the application of wafer fabrication, state duration dependency is considered. Experimental analyses based on real data demonstrate the effectiveness of the HSMM and reveal some managerial insights.